CONTEMPORARY CLINICAL APPLICATIONS OF COLCHICINE IN CARDIOVASCULAR AND INFLAMMATORY DISEASES - Olga Tatarata; Maja Osuch; Maciej Osuch; Martyna Jaciubek; Amanda Abramowicz; Magdalena Rumin; Anna Kiełboń; Zuzanna Olga Reklewska; Kornelia Domagała; Carmena Luty (International Journal of Innovative Technologies in Social Science, 2026)
Colchicine, an alkaloid derived from Colchicum autumnale, has gained renewed attention in contemporary medicine following advances in the understanding of inflammation as a central mechanism in cardiovascular and systemic inflammatory diseases. The objective of this narrative review was to synthesize clinical evidence published between 2015 and 2025 regarding the modern therapeutic applications of colchicine. A structured review of peer-reviewed randomized controlled trials, meta-analyses, and international guideline documents was performed, and findings were qualitatively integrated. Current rheumatology guidelines confirm colchicine as a first-line therapy for acute gout flares and for prophylaxis during urate-lowering treatment. In cardiology, guideline recommendations support its use in acute and recurrent pericarditis. Large randomized trials in patients with recent myocardial infarction and chronic coronary disease demonstrated a reduction in major adverse cardiovascular events when colchicine was added to contemporary standard therapy, and subsequent meta-analyses further evaluated its role in secondary cardiovascular prevention. Recent European guidelines for chronic coronary syndromes state that low-dose colchicine should be considered in selected patients as part of an event-prevention strategy. Additional studies suggest benefit in inflammation-related atrial fibrillation, particularly in postoperative settings, although gastrointestinal adverse events remain the most frequently reported side effects. Colchicine was also investigated in non-hospitalized patients during the COVID-19 pandemic. Overall, contemporary evidence supports colchicine as an established anti-inflammatory therapy with validated rheumatologic and expanding cardiovascular applications, while emphasizing the importance of careful patient selection and safety monitoring.